PENERAPAN RELATIONSHIP MARKETING DALAM SALURAN DISTRIBUSI - I Made Sukresna (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT The relationship marketing concept has long been became interest of academics and practitioners in marketing field. This concept has been applied to some aspects of marketing, also in distribution channel. However, it has been found that in reality, this concept were not always fit to be applied in all exchange relationship between manufacturers and distributors. This article elaborates the concept of relationship marketing, the contexts for fit conditions of relationship marketing application in distribution channel, and eventually ended with the way of effective relationship marketing’s  application in distribution channel. Key words: realtionship marketing; manufacturer and distributor relationship; distribution channels